2021
DOI: 10.1111/bjdp.12394
|View full text |Cite
|
Sign up to set email alerts
|

The recognition of emotional prosody in students with blindness: Effects of early visual experience and age development

Abstract: This study examined the role of early visual experience and age in the recognition of emotional prosody among students with visual impairments in China. A total of 75 primary and junior high school students participated in the study. The ability of participants to recognize the prosody of four basic emotions (sadness, anger, happiness, and neutrality) was explored. The findings were as follows. (1) Early visual experience had a significant effect on the recognition of emotional prosody. The accuracy rate of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A further avenue to gather evidence on the effect of visual calibration could be the investigation of late onset blindness: late blind individuals have lost the sense of sight later in life, implying that vision was present at the critical period needed for calibration. A sensory calibration hypothesis would therefore not predict an impairment at a vocal discrimination task in late blind compared to EB subjects (cf., Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further avenue to gather evidence on the effect of visual calibration could be the investigation of late onset blindness: late blind individuals have lost the sense of sight later in life, implying that vision was present at the critical period needed for calibration. A sensory calibration hypothesis would therefore not predict an impairment at a vocal discrimination task in late blind compared to EB subjects (cf., Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to emotional signals, developmental studies have shown that blind children and adolescents are worse and slower than the sighted when discriminating prosodies of emotional sentences (Chen et al, 2021) and have difficulties at recognizing vocal expressions of emotions (Blau, 1964; Dyck et al, 2004; Minter et al, 1991). Furthermore, blind children face challenges in emotion regulation (Chennaz et al, 2022) and have difficulties expressing emotions and reading other people’s mind (Roch-Levecq, 2006).…”
mentioning
confidence: 99%
“…A sensory calibration hypothesis would therefore not predict an impairment at a vocal discrimination task in late blind compared to early blind subjects (cf. Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Not only are the prevalence rates of students who are blind or have low vision increasing (Varma et al, 2017), these students and their families are increasingly aware of the opportunities for educational success and are more readily available when their teachers provide needed differentiated instruction. Providing educational supports for students who are blind or have low vision is essential to their development because severe vision impairment is associated with long-term delays in motor development, language, social-emotional development, and overall cognitive functioning (Adelson & Fraiberg, 1974;Chen et al, 2022;Wakefield et al, 2006). Without appropriate resources and supports, school-age children who are blind or have low vision are likely to experience lower levels of educational success (Flaxman et al, 2017).…”
mentioning
confidence: 99%